Virtual Team Citizenship Behaviors: Scale Development and Validation - (:unkn) unknown (My University, 2013)
Organizational citizenship behaviors (OCBs) are the extra-role, voluntary behaviors performed by organization members for the benefit of the organization. These behaviors have been widely studied and several dimensions have been defined. However, the majority of the work on OCBs focuses on traditional organizations where all employees are collocated and can interact on a regular basis. With the changing workplace, employees can now work remotely or across different locations and still be expected to work together. Those employees who are not collocated may not feel the need to benefit the organization, but may feel connected to the team and therefore participate in virtual team citizenship behaviors (VTCBs). This paper reviews the current OCB literature by defining OCBs, reviewing the empirical literature, and providing a critique of the current literature. Next, a framework for studying VTCBs is developed based on virtual team literature. I define and discuss the differences between VTCBs and OCBs. Next, I develop propositions for assessing construct validity using multiple validation approaches, including convergent, and divergent, and nomological validity. I then propose and conduct three interlocking studies to generate items for the scale (Study 1), to assess the dimensionality and psychometric properties of the scale and establish convergent and divergent validity (Study 2), and to test the proposed nomological model (Study 3). The results of each study and the implications of the studies are discussed.
Keywords: Organizational Citizenship Behavior; Virtual Teams